ANALISIS PERBANDINGAN PROFITABILITY, EFFECTIVE GOVERNANCE AND FIRM MARKET VALUE PADA PERUSAHAAN ESG/SRI (STUDI EMPIRIS PERUSAHAAN BESAR DI INDONESIA) - Eko Dwi Putra; Fajri Adrianto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
In this paper we study the effect of a ESG/SRI label on profitability, corporate governance, and firm market value, evidence from Indonesia’s top listed firms. Recent evidence indicates that listed firms with ESG/SRI label has better RoE, value, governance, and capacity for growth. The samples used in this study are companies that are included in the SRI-KEHATI Index members and outside the SRI-KEHATI index, which amount to 38 companies in the 2014-2018 period, total observations of 190. We used Least Square Dummy Variable (LSDV) and Multivariate analysis to determine the effect of all the variables involved. We find significant effect of ESG/SRI label from profitability, corporate governance, and firm value. We show that SRI label adds about 8.9 percentage points of RoE, however NON-SRI label adds about 18,6 percentage  points of firm’s value and more effective 10.2 percentage point of governance quality. Finally, we find that Effective Corporate Governance will increase profitability (ROE) and firm’s value (Tobin’s Q).